Hindu versus christian perspectives on victory, god’s will and love: a comparative study - Mahmoud, Amel; Abdulkarim, Chiad (Humanities Journal of University of Zakho, 2023)
This research paper investigates two literary texts, one is an ancient Indian epic Bhagavad Gita (The Song of the Lord) anonymously written between (500 -200 BC) while the second is a historical novel Manuscript Found in Accra by Paulo Coelho. Though the two texts may vary in their genre and their religious tradition, they still share significant features. The first is related to the setting. The first shared feature is army preparation for a war which is going to happen soon based on the setting of both texts. The second feature, in common with the two texts, is in connection with their narrative structures. Both texts are based on a question-answer dialogue, a discourse between two parties of characters. The third significant characteristic shared by the two texts is in connection with their core religious, spiritual, and philosophical themes. Arjuna, in Bhagavad Gita, and the people of Jerusalem, in Manuscript Found in Accra, agitatedly ask their spiritual leaders, Krishna, in the first text, and the Copt, in the second, religious and ethical questions. These questions evidently refer to key subjects which are victory in a military combat, God’s will and volition and love between man and God and among human beings. While analyzing these themes, the discussion thoroughly probes through the two texts’ religious contexts: the Hindu theologian tradition and Biblical teachings. The aim is to meticulously examine the points of disparity between the Hindu versus the Christian understanding of victory in the battlefield, God’s will and love, which are the core themes in this analysis.